Drip irrigation of rice A water saving technology for enhancing profitability and environmental security - Rao, V Praveen; Anitha, V; Rao, A Subba (Indian Farming, 2021)
The use of drip irrigation in aerobic rice cultivation is a contemporary water-saving strategy. However, inadequate evidence concerning technical feasibility i.e., crop establishment method, planting pattern, drip product and design module, productivity levels, resource conserving capacity and economic viability limited its use in irrigated rice. The results indicate that drip irrigation of aerobic rice not only enhances grain yield but also contributes to water, energy, and fertilizer savings compared to conventional transplanted flood method of irrigation. These incentives are the key to scaling the adoption of water-saving technologies in rice, thereby enabling rapid food grain production growth through sustainable intensification to meet the future food demand of growing population under declining resources. The present policies like PMKSY (Pradhan Mantri Krishi Sinchayee Yojana) at national and state level water conservation policy initiatives such as â€œTelangana State Micro Irrigation Projectâ€, â€œAndhra Pradesh Microirrigation Projectâ€ and â€œGujarat Green Revolution Companyâ€ are aimed to address higher water productivity in agriculture in water-scarce situations. Major challenges to the large-scale adoption of water-saving technologies include farmersâ€™ lack of knowledge about technical and economic feasibility of drip irrigation, traditional habits of cultivating rice and poor linkages among stakeholders. Continued support of research and extension agencies is hence imperative to ensure the effective scaling up of drip irrigation technology among rice farmers in the country.